Preconditioning strategies to limit graft immunogenicity and cold ischemic organ injury - Woude, Fokko J. van der; Schnülle, Peter; Yard, Benito A. (Journal of investigative medicine, 2004)
During the transplant process, the graft is exposed to numerous events, which may enhance its immunogenicity. In particular, factors related to brain death, such as hemodynamic instability and systemic release of cytokines, cold preservation on harvesting, and reperfusion injury, are known to accumulate in harm, conveying a proinflammatory state to the graft before transplant. Alloimmune reactivity is initiated when the host immune system detects non-self-antigens in the context of "danger signals." Eliminating these danger signals by modifying the graft before transplant has the potential to attenuate the alloimmune response. The molecules, which mediate danger signals, have not yet been fully identified. Free oxygen radicals and interferon-gamma are important candidates. One of the most important protective mechanisms against oxidative stress is the heme oxygenase 1 system. Up-regulation of heme oxygenase 1 in grafts has been shown to prevent ischemia-reperfusion damage and improve long-term graft survival in various transplant models. The benefit of blocking the action of interferon-gamma in kidney transplants is less clear because the compound plays such a complex and pivotal role in the immune response, and experimental data with interferon-gamma receptor knockout mice are conflicting. It has recently become clear that catecholamines are important graft-modifying agents. Dopamine is capable of stimulating the induction of protective enzymes like heme oxygenase-1 (HO-1) rendering the organ more resistant to the insult of ischemia/reperfusion and inflammation. Retrospective clinical data suggest that treatment of brain-dead organ donors with catecholamines is associated with less rejection and a better long-term graft survival of kidneys transplanted from these donors. Catecholamines can also modulate cytokine production and prevent cold-induced damage. Other substances, such as proteoglycans and phosphatidylethanolamine-bound hyaluronic acid, may interfere with the actions of interferon-gamma. Further studies of these compounds in experimental animal models and in prospective randomized clinical trials will help establish their efficacy in donor pretreatment. It is important to underscore that donor pretreatment will have great advantages for the recipient because an improved long-term graft survival could thus be achieved cost-efficiently and without great effort or side effects.
Gesehen am 31.05.2022